Group Medical Visits: experiences with patient and resident implementation. Issue 1 (2nd January 2020) - Kirk, Julienne K; Boyd, Charlotte T; Spangler, John G; Strickland, Carmen G
ABSTRACT: Objective : Patients with diabetes must navigate multiple components of care to self-manage their disease. Group Medical Visits (GMVs) are a forum for patients to see a provider as well as actively participate in education and care management with other patients with diabetes. The objective is to describe GMV implementation and resident involvement in a primary care setting. Methods : We adapted and implemented a GMV model into a primary care practice with a residency program. Residents attend GMV sessions that provide a continuity experience in addition to their regular clinic schedules. A cohort of patients enroll in a series of eight GMVs occurring over of 4 months. Each patient and resident complete surveys evaluating the visits. Results : There have been 14 GMV groups totaling 70 participants. GMV groups (N = 67) mean A1C for reduction was 0.53 ± 1.60 from baseline to 3- to 6-month post-GMV follow-up. Resident and patient feedback show an overall positive experience. Conclusion: The GMV model offers patients the setting to interact and exchange experiences with each other as well as to receive feedback from providers and the health-care team.  The incorporation of the GMV program into residency training provides a continuity group care experience and an alternative practice model.